Eremotherium laurillardi (Lund, 1842) (Xenarthra, Megatheriinae) is the only valid megatheriine sloth species in the Pleistocene of intertropical Brazil: A response to Faure et al., 2014 - Cartelle, Cástor (2014)
Recent reports (Faure et al., 2014; Guérin and Faure, 2000, 2008) describe the existence, in intertropical Brazil, of a small (“dwarf”) megatheriine sloth, Eremotherium laurillardi (Lund, 1842), and a giant-sized megatheriine, Eremotherium rusconii (Schaub, 1935). This view is in marked contrast to that advanced by Cartelle and De Iuliis (1995, 2006), who demonstrated the presence of a single Late Pleistocene giant Eremotherium species, for which the valid name is Eremotherium laurillardi (Lund, 1842), in intertropical Brazil and elsewhere in America. These authors dubbed this species the Panamerican giant ground sloth. The present contribution reviews the material discussed by Faure et al. (2014) and demonstrates that it belongs to a juvenile (as did the material from Guérin and Faure, 2000) of the Panamerican giant ground sloth (i.e., E. laurillardi sensu Cartelle and De Iuliis, 1995, 2006) and that there is no evidence of a dwarf megatheriine in the Late Pleistocene of intertropical Brazil.